2012
DOI: 10.1007/s00580-012-1620-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of CYP2C9 gene polymorphisms on response to treatment with sulfonylureas in a cohort of Egyptian type 2 diabetes mellitus patients

Abstract: Oral hypoglycemics are a widely prescribed group of drugs for the management of type 2 diabetes mellitus. Sulfonylureas (SUs) are the cornerstone of type 2 diabetes pharmacotherapy. The enzyme cytochrome P450 2C9 (CYP2C9) is the main enzyme that catalyzes the biotransformation of SUs. It is encoded by the polymorphic gene CYP2C9 with two allelic variants namely CYP2C9*2 and CYP2C9*3 coding for variant allozymes with reportedly decreased metabolic capacity resulting in decreased SUs clearance and consequently p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 23 publications
(16 reference statements)
1
4
0
Order By: Relevance
“…Reports from healthy Swedish populations (25) consider its carriers to be lower rate metabolizers, whereas studies on Ecuadorians regard them to possess an increased CYP2C9 hydroxylation capacity (26). When comparing the frequency of variant *1 / *2 in the Mexican population from the present study with those from other regions of the world identified in previous studies, significant differences were identified respect to Europe (0.06 vs. 0.18-0.24; P<0.05) and Africa (0.06 vs. 0.20; P<0.05), but not respect to India (21,32-38). As for *1 / *3 , statistical differences were identified in the Mexican population when compared with European countries (32-38), India (39), China (40), Japan (41) and Egypt (21) (P<0.05; Table IV).…”
Section: Resultssupporting
confidence: 43%
See 3 more Smart Citations
“…Reports from healthy Swedish populations (25) consider its carriers to be lower rate metabolizers, whereas studies on Ecuadorians regard them to possess an increased CYP2C9 hydroxylation capacity (26). When comparing the frequency of variant *1 / *2 in the Mexican population from the present study with those from other regions of the world identified in previous studies, significant differences were identified respect to Europe (0.06 vs. 0.18-0.24; P<0.05) and Africa (0.06 vs. 0.20; P<0.05), but not respect to India (21,32-38). As for *1 / *3 , statistical differences were identified in the Mexican population when compared with European countries (32-38), India (39), China (40), Japan (41) and Egypt (21) (P<0.05; Table IV).…”
Section: Resultssupporting
confidence: 43%
“…The first stage of the present study described the variability and substantial diversity of the distribution of CYP2C9 within samples from Mexican patients with DMT2 and those from other populations; however, the effect of this genetic factor accounts for only 40% of the glibenclamide response variability (17), and it has only been studied in two other populations (20,21). The function of these polymorphisms in differential glibenclamide dosages, their effect on the variability of the response monitored by HbA1c (considered to be the main efficacy biomarker in the present study) and also on the most relevant adverse glibenclamide reaction (including hypoglycemia), have yet to be reported.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The next study determined the impact of CYP2C9 polymorphism on response of treatment in Egyptian patients with DMT2 [13]. The genotype frequencies are 53 patients who were carriers of CYP2C9 *1/*1 (wild-type), 20 patients who were carriers of CYP2C9 *1/*2 (heterozygous for CYP2C9*2), 18 carriers of CYP2C9 *1/*3 (heterozygous for CYP2C9*3) and 9 patient carriers of CYP2C9 *2/*3 (double heterozygous for both mutant alleles).…”
Section: Discussionmentioning
confidence: 99%